Associations between human non‐motorised recreational activity on nest box occupation, exploratory behaviour and breeding success in a passerine bird - Utku Urhan; Kim Platjouw; Peter P. de Vries; Eva Serrano Davies; Kees van Oers (Journal of Avian Biology)
Anthropomorphic activities have a large impact on ecosystems in many ways, one of which is how animals behave. Non‐motorised nature recreation is a popular human activity of which the impacts on nature are largely unknown. These activities, which include hiking, biking, pet walking and horseback riding, tend to increase during the commencement of the breeding activity for most passerine forest birds in temperate zones. We here investigated whether variation in recreational activity associates with patterns of nest box occupation and reproductive success in a long‐term study of personality‐typed great tits Parus major. We measured human disturbance in the area by recording the frequency of non‐motorised recreational activities by observations. We were particularly interested in the relationship between disturbance levels and nest box occupancy as well as the relationship between disturbance levels of occupied nest boxes and exploratory scores of the great tits that occupied them. We also investigated whether reproductive characteristics such as fledging success, clutch size, chick weight and tarsus length varied with disturbance levels at occupied nest boxes. We did not find a direct association between nest box occupation and disturbance. Habitat quality rather than disturbance explained the nest occupation. Furthermore, more exploratory individuals occupied boxes in less disturbed areas, independent of habitat quality. Fitness decreased with increasing disturbance independent of habitat quality. Chicks were heavier and had longer tarsi, and clutch sizes were bigger in less disturbed areas. In conclusion, we found breeding site choice of great tits to be independent of human activity, although there are clear fitness effects of human disturbance.